(untitled) (The Journal of Theoretical Accounting Research, 2026)
Accountants are often stereotyped as rigid, detail-oriented “bean counters” while marketers and salespersons are viewed as more dynamic. These stereotypes have possible implications for cross-functional team success, especially when viewed through the lens of organizational conflict theory. This study explores whether accountants differ from marketers and salespersons in terms of personality, as well as how each group perceives accountants’ attributes that are deemed critical to team success. We find no significant personality differences between accountants and their marketing and salespersons counterparts. However, perceptions of the accountant differ. The accountant views the workplace attributes of accountants more favorably than marketers and salespersons. Additionally, demographic factors such as experience appear to influence perceptions, with more seasoned professionals expressing fewer positive views of accountants. These findings provide insights for leaders managing cross-functional teams, highlighting that although personality may not drive conflict, perception gaps remain a roadblock for team success.